Resistance training prevents right ventricle hypertrophy in rats exposed to secondhand cigarette smoke - Rippi Moreno, Ana Caroline [UNESP]; Nai, Gisele Alborghetti; Laurindo, Caroline Pancera [UNESP]; Rego Gregorio, Karen Cristina [UNESP]; Olean-Oliveira, Tiago [UNESP]; Souza Teixeira, Marcos Fernando [UNESP]; Seraphim, Patricia Monteiro [UNESP] (Public Library of Science (PLoS), 2020)
Exposure to secondhand cigarette smoke is associated with the development of diverse diseases. Resistance training has been considered one of the most useful tools for patients with pulmonary disease, improving their quality of life. This study aimed to evaluate the effect of resistance training (RT) on the prevention of thickening of the right ventricle wall of rats exposed to secondhand cigarette smoke. Thirty-two Wistar rats were divided into four groups: Control (C), Smoker (S), Exercised (E) and Exercised Smoker (ES). The smoker groups were exposed to the smoke of four cigarettes for 30 min, twice daily, five days a week, for 16 weeks. The exercised groups climbed on a vertical ladder with progressive load, once a day, five days a week, for 16 weeks. The heart, trachea, lung, liver and gastrocnemius muscle were removed for histopathological analysis. Pulmonary emphysema (S and ES vs C and E, P < 0.0001) and pulmonary artery thickness enlargement (S vs C and E, P = 0.003, ES vs C, P = 0.003) were detected in the smoking groups. There was an increase in the right ventricle thickness in the S group compared with all other groups (P < 0.0001). An increase in resident macrophages in the liver was detected in both smoking groups compared with the C group (P = 0.002). Additionally, a relevant reduction of the diameter of the muscle fibers was detected only in ES compared with the C, S and E groups (P = 0.0002), impairing, at least in part, the muscle mass in exercised smoking rats. Therefore, it was concluded that resistance training prevented the increase of thickness of the right ventricle in rats exposed to secondhand cigarette smoke, but it may be not so beneficial for the skeletal muscle of smoking rats.